Postoperative Bowel Herniation in a 5-mm Nonbladed Trocar Site - Huang, Marilyn (Society of Laparoendoscopic Surgeons, 2010)
BACKGROUND: Incisional hernias are a rare complication of laparoscopic surgery, with a reported incidence of <1%. CASE REPORT: We describe a case of bowel herniation and strangulation involving a 5-mm trocar site. CONCLUSION: Although there is growing literature supporting fascial closure of abdominal port sizes ≥10mm, there is sparse data to suggest closure of 5-mm port sites. Our case illustrates that in appropriate clinical scenarios, the possibility of a strangulated hernia involving a 5-mm port site warrants consideration.